Kasasi Atas Dasar Judex Facti Salah Menerapkan Hukum Dalam Perkara Kesusilaan Oleh Anggota Militer - Ghazi Leomuwafiq; Kristiyadi, S,H., M.Hum - (Verstek, 2017)
This Research aim is to find out the suitability of the the appeal on the basis missaplied the law in the case of decency by members of the military with Act No. 31 of 1997 on the military Judiciary. The research method used was the normative legal research that is both prescriptive and applied. The approach used is case approach. The case of decency committed by Mayor Rudy Chb Pamungkas Santoso is members of the military have been terminated with the decision of a court martial II jakarta Number 13-K/PMT-II/CE/V/2012 pidan prison sentence by dropping the 7 (seven) months and additional criminal was dismissed from the service of the milter. Against the verdict of the appeal which is then terminated with a military court ruling Jakarta Main number: 17-K/PMTU/BDG/AD/VII/2014 that freeing the defendants for not proving to legally perform criminal acts of decency. A military judge advocate then apply for cassation with reasons judex facti wrong applying the law. The filing of the appeal by the Military judge advocate accepted by the Supreme Court with the ruling of the Supreme Court of the Number 45 k/MIL/2015, which cancels the previous ruling. Based on research can be concluded on the basis of Cassation submissions wrongly applied the law was in accordance with the provisions article 239 of law No. 31 of 1997. So the filing of Cassation on the basis of acceptable law wrongly.        Key word: Cassation, Morality, Military Members